Pertanggungjawaban Penyedia Jasa Telekomunikasi Atas Kerugian Daur Ulang Nomor SIM Card di Kota Gunungtua Perspektif Maslahah Mursalah - Silvi Aznidar Siregar; Sahliah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The practice of recycling SIM card numbers by telecommunications providers often results in losses for existing customers, such as misuse of personal data and communication disruptions. This research aims to identify the types of losses experienced by customers due to the recycling of SIM card numbers and to analyze the accountability of telecommunications service providers for the losses incurred from the recycling of SIM card numbers from the perspective of Maslahah Mursalah. This type of research is empirical legal research with a living case studies approach, a statute approach, and a conceptual approach. Data is collected using interviews and document studies. The data is then processed and analyzed using qualitative methods. The results of this research indicate that the practice of recycling SIM cards in Gunungtua city leads to losses such as financial losses, reputational damage, and privacy breaches. In the perspective of maslahah mursalah, customers feel that the recycling of the number does not provide them with benefits compared to the operators who gain many advantages and profits. A review of the maslahah mursalah concerning the practice of recycling SIM card numbers indicates that if the harms outweigh the benefits, then it is not permissible. Furthermore, telecommunications service providers must be held accountable for any losses experienced by customers due to the practice of recycling SIM card numbers.